A Prospective Study on Assessment of the Drug Interventions During Ward Rounds in the Department of General Medicine at a Tertiary Care Hospital. - Veena Gadicherla; Varun Dasari; Perli Kranti Kumar; Naga Latha Dhulipalla (International Journal of Allied Medical Sciences and Clinical Research, 2024)
The aim of the present study was a prospective study on assessment of the drug interventions during ward rounds in the department of general medicine at a tertiary care hospital. Out of 18 drug need not prescribed were 3(16.66%), inappropriate dosage form were 6(33.33%), wrong dose taken were 1(5.55%), dose too low were 3(16.66%), dose too high were (5.55%) and duration of treatment inappropriate were 4(22.22%). Highest number of interventions identified were minor 48.71%. Having highlighted the importance of clinical pharmacist in this study, a multidisciplinary team approach is required to effectively minimize the potential of drug related problems. Furthermore, the high degree of acceptance by prescribers encourages clinical pharmacists to continue their service and to extend it to other wards and departments. The present results point to the establishment of drug related problem reporting system at each hospital and to share data with other hospitals healthcare settings. Participation and interventions of clinical pharmacists in health care positively influence clinical practice. Many studies have monitored interventions in clinical areas to provide quantitative and qualitative data on pharmaceutical input.